The contemporary Irish detective novel - Mannion, Elizabeth (Crime files series., 2016)
Irish detective fiction has enjoyed an international readership for over a decade, appearing on best-seller lists across the globe. But its breadth of hard-boiled and amateur detectives, historical fiction, and police procedurals has remained somewhat marginalized in academic scholarship. Exploring the work of some of its leading writers--including Peter Tremayne, John Connolly, Declan Hughes, Ken Bruen, Brian McGilloway, Stuart Neville, Tana French, Jane Casey, and Benjamin Black--The Contemporary Irish Detective Novel opens new ground in Irish literary criticism and genre studies. It considers the detective genre's position in Irish Studies and the standing of Irish authors within the detective novel tradition.